2017
DOI: 10.1186/s12896-017-0343-8
|View full text |Cite
|
Sign up to set email alerts
|

Functional expression of a novel α-amylase from Antarctic psychrotolerant fungus for baking industry and its magnetic immobilization

Abstract: Backgroundα-Amylase plays a pivotal role in a broad range of industrial processes. To meet increasing demands of biocatalytic tasks, considerable efforts have been made to isolate enzymes produced by extremophiles. However, the relevant data of α-amylases from cold-adapted fungi are still insufficient. In addition, bread quality presents a particular interest due to its high consummation. Thus developing amylases to improve textural properties could combine health benefits with good sensory properties. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…Some strains of P. pannorum isolated from cold habitats produce abundant cold-adapted α-amylases, which indicates its significant role as a desirable candidate in food processing. He et al (2017) cloned the correlated gene AmyA1, and heterologously expressed it in Aspergillus oryzae . AmyA1 was also immobilised on magnetic nanoparticles and characterised.…”
Section: Representative Cold-adapted Fungal Speciesmentioning
confidence: 99%
“…Some strains of P. pannorum isolated from cold habitats produce abundant cold-adapted α-amylases, which indicates its significant role as a desirable candidate in food processing. He et al (2017) cloned the correlated gene AmyA1, and heterologously expressed it in Aspergillus oryzae . AmyA1 was also immobilised on magnetic nanoparticles and characterised.…”
Section: Representative Cold-adapted Fungal Speciesmentioning
confidence: 99%
“…The latest example of novel cold-active α-amylase (AmyA1) isolated from Antarctic psychrotolerant fungus (Geomyces pannorum) and its application in baking industry is reported by He et al [32]. The study revealed that AmyA1 would have a great potential in traditional baking and food industry.…”
Section: Cold-active Enzymes In Food Technologymentioning
confidence: 99%
“…Macromolecules are hydrolyzed into polypeptides, dipeptides and amino acids, and then further decomposed into small molecules of organic acids by deamination, ammonia and carbon dioxide. That makes the decline of COD and VSS, and the rise of NH 4 + -N and Polysaccharide. [16] …”
Section: Orthogonal Testmentioning
confidence: 99%
“…Among all these carriers, magnetic nanoparticles can overcome the inconvenience in recycling and handling which can be recovered easily from reaction solutions by simple magnetic capture. [4] 2. Material and Methods…”
Section: Introductionmentioning
confidence: 99%